Factors Associated with Successful Smoking Cessation Program at Public Health Clinics in Perlis - Soo Pei Pei; Nurfaizah Azmi; Nur Aqilah Tahirah Abdul Munir; Nurulaishah Mohmmad; Ng Yit Han (Asian Journal of Medicine & Health Sciences, 2024)
Cigarette smoking is widely recognized as the most preventable risk factor for non-communicable diseases. This study aimed to determine the prevalence of successful smoking cessation and to identify factors associated with successful smoking cessation for patients recruited in the Quit Smoking Clinics in Perlis. This is a retrospective study reviewing the Stop Smoking Service Registry records obtained from the Quit Smoking Clinics from July to December 2022. Success in quitting smoking was defined as abstaining from smoking for at least six months following the initial appointment. Multiple logistic regression was used to identify factors associated with successful quit smoking. A total of 165 patients enrolled in the Quit Smoking Clinics in Perlis. Most of the patients were male (n=160, 97.0%), married (n=146, 88.5%), and Malay (n=149, 90.3%). More than 40% of patients seeking guidance from the clinics were able to quit smoking successfully. Those who stay near the clinic (